Działania organów bezpieczeństwa i porządku publicznego jako formy prewencyjnego ingerowania w wolność wypowiedzi - Taczkowska-Olszewska, Joanna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The paper demonstrates (by means of description and analysis) that the following activities of the law enforcement organs exemplify the limitation of the freedom of speech: (1) removal of the tent of the Solidarni 2010 movement from Krakowskie Przedmieście in Warsaw; (2) the erection of safety barriers in front of a group of people praying before a cross standing in front of the Chancellery of the President of Poland; (3) the Internal Security Agency entering the apartment of a student who designed the Antykomor.pl website, publishing negative opinions about the way the incumbent Polish President is exercising his office; (4) the removal by the Speaker of the Senate of part of an exhibition about the Smoleñsk catastrophe presented in the Parliament building; (5) arresting two young men and taking them to the police station to be questioned for holding a banner reading “It’s time for Antykomor. Freedom of speech is unhealthy;” (6) imposing fines of PLN 500.00 (roughly equivalent to EUR 125) on football fans demonstrating in front of the Chancellery of the Prime Minister with a banner reading “Donald, you moron, football fans will topple your government;” (7) checking the IDs of people laying flowers in Krakowskie Przedmieście to commemorate the anniversary of the Smoleñsk catastrophe; and (8) the Municipal Guard blocking the way, in order to prevent members of the Polish parliament from attending a celebration commemorating the Smoleñsk catastrophe.